PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GQGA UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SDN 014 PEMATANG SIKAT KECAMATAN RIMBA MELINTANG - Antosa, Zariul Antosa Zariul; Daud, Damanhuri Daud Damanhur; ', Juniati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem this research is the student achivement of PKN Fourth garders studies still low with an average value 6.0 and minimum completeness criteria ( KKM ) PKNis 65. Between students amounting to 25 pepole only 7 students who achieve clasical KKM.  This research is classroom action Research ( CAR ). Which aims to improve the student achievement of PKNsudies clas IV at SDN 014 Pematang Sikat with implementation cooperative learning model GQGA. Formulation of the problem : Is the implementation of cooferative learning model GQGAcan improve students achivement of PKNsyudies at SDN 014 Pematang Sikat. Subjects were students Of SDN 014 Pematag Sikat. Totalling 30 people who use the data source, the data collection intruments in this thesis present the result obtained each day before the action improved in base score cycle with the average being 62. In the first cycle improve in average  of 70 and an improve second cycle with an average of 76,6. Activities of the teacher in the learning process at the cycle one 64,3%  and 74.3% and in the second cycle improved. So  the result in class IV SDN 014 Pematang Sikat that the implementation of cooperatiff learning model GQGAcan Improved the student Achivement of PKNstudies at fourth graders SDN 014 Pematang Sikat. Keyword : cooperatiff learning model GQGA, The result of PKn